The marvelous ones: drugs, gang violence, and resistance in East Los Angeles - Contreras, Randol (University of California Press, 2024)
"Once celebrated in the gang world as rebels who defied the established prison order, veterano Maravilla gang members now grapple with the consequences of leading violent and drug-ridden lives. At once thrilling and tender, The Marvelous Ones sheds light on how these aging gang members struggle to stay meaningful in the face of addiction, violent trauma, and a rapidly changing East Los Angeles. Randol Contreras spent close to a decade studying the legendary Maravilla gangs of East LA, who made waves in the 1990s for their rebellion against the most powerful prison gang in the United States: the Mexican Mafia, or La Eme. These men granted Contreras unique access to their experiences, revealing how family members shun them, how jail and prison worsen them, how the church and drug treatment redeem them, and how their brightest moments lie in their pasts as legends of the California gang world. The Marvelous Ones gives human faces to the suffering and resilience of some of the most marginalized members of our culture"--